Sociotechnical Adaptation of Telerehabilitation in Rehabilitation Practice: Survey Among Rehabilitation Professionals - Tuija Partanen; Riitta Seppänen-Järvelä; Sinikka Hiekkala; Jari Lindh (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundBoth rehabilitation practice and rehabilitation professionals’ work have been transformed by the adoption of different technological solutions. Sociotechnical theory can be used to analyze the adoption of technologies in rehabilitation practice. ObjectiveThis study aimed to enhance the understanding of the sociotechnical perspective of telerehabilitation (TR) in rehabilitation practice, as well as the understanding of how sociotechnical frameworks can be used to examine the implementation of telerehabilitation in outpatient rehabilitation. MethodsA survey of rehabilitation professionals (N=629) was conducted in a Finnish outpatient rehabilitation setting. Data from 5 open-ended questions were analyzed using inductive, deductive, and abductive qualitative content analysis. An analysis matrix formed from the Fit between Individuals, Tasks, and Technology (FITT) and the Fit between Individuals, Tasks, Technology, and Environment (FITTE) frameworks was used. ResultsDeductive analysis revealed that in individual-task fit, professionals’ and clients’ adequate skills, support for participation, and a positive attitude were essential. The task-technology fit highlighted the need for the professionals’ familiarization, changes in methods and materials, and collaboration with clients and their close associates and networks. The individual-task fit revealed that professionals found TR tasks to be more complex than those in in-person practice and that TR increased professionals’ perceived workload and clients’ need for personal contact, especially during the familiarization phase. Our findings suggest that certain dimensions of the FITTE framework need to be specified in order to better understand the sociotechnical adaptation of TR. ConclusionsWe propose an extension to create the Fit between Individual, Task, Technology, Interactive Sociotechnical Environment, and Organizational and Sociopolitical Context (FITTIO) framework, which provides conceptual tools for making contextual interpretations of the adoption of TR in rehabilitation settings. This study increases understanding of the sociotechnical nature of TR, which can be used in the adoption of technological solutions in rehabilitation practice.